Rapprochement sebagai Pendekatan Sirkulatif dalam Membangun Intersubjektivitas Studi Agama - Abbas Sofwan Matla'il Fajar; Hamdan Maghribi (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2021)
The "rapproachment" is a way of reading religious paradigms that lead to the intersubjectivity of religious studies. Kim Knott as a researcher who focuses on the field of religious studies in providing new offers in the methodology of religious studies. This arises because of the many obstacles faced by academics in various universities regarding religious studies, starting from stagnation in methodology and approaches. Kim Knott's offer is based on two approaches, namely outsider and insider, then she developed into four elements, on the outsider includes pure researchers and researchers as participants, while in insider includes pure participants and participants as researchers, then to sharpen the objectivity of the research he offers a circular approach between subjects and object towards inter-subjectivity called the 'rapprochement' approach as reflective links that complement each other and lead to the intersection between religions.